2008
DOI: 10.1074/jbc.m802081200
|View full text |Cite
|
Sign up to set email alerts
|

Histone Acetylation and Methylation at Sites Initiating Divergent Polycistronic Transcription in Trypanosoma cruzi

Abstract: Trypanosomes are ancient eukaryotic parasites in which the protein-coding genes, organized in large polycistronic clusters on both strands, are transcribed from as yet unidentified promoters. In an effort to reveal transcriptional initiation sites, we examined the Trypanosoma cruzi genome for histone modification patterns shown to be linked to active genes in various organisms. Here, we show that acetylated and methylated histones were found to be enriched at strand switch regions of divergent gene arrays, not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 55 publications
4
90
0
Order By: Relevance
“…The lack of an extensive basic surface on trypanosome TFIIB may reflect a relaxed specificity of tRNAP-II orientation at promoters in trypanosomes. Most trypanosome protein-encoding genes are transcribed in large arrays that appear to initiate bidirectionally from strand switch regions (35)(36)(37). Weak specificity of preinitiation complex orientation could cause bidirectional transcription from strand switch regions.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of an extensive basic surface on trypanosome TFIIB may reflect a relaxed specificity of tRNAP-II orientation at promoters in trypanosomes. Most trypanosome protein-encoding genes are transcribed in large arrays that appear to initiate bidirectionally from strand switch regions (35)(36)(37). Weak specificity of preinitiation complex orientation could cause bidirectional transcription from strand switch regions.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies against tagged H2AZ and H2BV gave peaks of enrichment coincident with antiH4K10ac, suggesting that transcription start sites are characterized by nucleosomes containing H2AZ, H2BV, and H4K10ac. Previous studies showed that H2BV-containing nucleosomes are enriched in trimethylated H3K4 (Mandava et al 2008) and that divergent SSRs are also enriched with acetylated H3 (Respuela et al 2008).…”
Section: Trypanosome Histone Variants and Transcriptionmentioning
confidence: 99%
“…Neighboring transcription units can be either convergent or divergent, and the regions between them are known as strand switch regions (SSRs). Nuclear runon assays in the related trypanosomatids Leishmania major and Trypanosoma cruzi, which are highly syntenic with T. brucei (El-Sayed et al 2005), showed that RNA polymerase II (pol II) transcription initiates at divergent SSRs and terminates at convergent SSRs (MartinezCalvillo et al 2003(MartinezCalvillo et al , 2004Respuela et al 2008). Trypanosome genomes, however, lack recognizable pol II promoter elements (Clayton 2002).…”
Section: Trypanosome Histone Variants and Transcriptionmentioning
confidence: 99%
“…It would be also interesting to analyze the genomic distribution of histone variants in Leishmania. In T. cruzi sequencing of DNA from ChIP experiments revealed that acetylated and methylated histones were found to be enriched in TSS but not in TTS [122].…”
Section: Molecular Interactions On Chipmentioning
confidence: 99%